2011
DOI: 10.1371/journal.pone.0020232
|View full text |Cite
|
Sign up to set email alerts
|

The Sea Peoples, from Cuneiform Tablets to Carbon Dating

Abstract: The 13th century BC witnessed the zenith of the Aegean and Eastern Mediterranean civilizations which declined at the end of the Bronze Age, ∼3200 years ago. Weakening of this ancient flourishing Mediterranean world shifted the political and economic centres of gravity away from the Levant towards Classical Greece and Rome, and led, in the long term, to the emergence of the modern western civilizations. Textual evidence from cuneiform tablets and Egyptian reliefs from the New Kingdom relate that seafaring tribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…The best modeled transition between Strata 1-5a and 1-4 ranges between 1140 and 1095 BC at ±1σ confidence level. Since Stratum 1-5c contains an LH IIIC bowl associated (Kaniewski et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The best modeled transition between Strata 1-5a and 1-4 ranges between 1140 and 1095 BC at ±1σ confidence level. Since Stratum 1-5c contains an LH IIIC bowl associated (Kaniewski et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The presence of M527 in Provence, southern Italy and Ukraine may reflect subsequent Greek maritime Iron Age colonization events 16 and perhaps, given its appearance among the Druze and Palestinians, even episodes associated with the enigmatic marauding Sea Peoples. 42 The hg G2a3b1c-L497 sub-cluster, on the other hand, has so far been found essentially in European populations and therefore is probably autochthonous to Europe. While acknowledging that the inference of the age and geographic source of dispersals of Y chromosome haplogroups from the frequency and STR diversity data can be approximate at best, we speculate that this lineage could potentially be associated with the Linearbandkeramik (LBK) culture of Central Europe, as its highest frequency (3.4-5.1%) and Td estimate (Supplementary Table S4) of 10 870 ± 3029 years ago occur there.…”
Section: Y-chromosome Haplogroup G Phylogeography S Rootsi Et Almentioning
confidence: 99%
“…1200 BC, with population migrations and wars. From this crisis arose new societies and new ideologies [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars are even uncertain whether the Sea People’s existence was a cause or an effect of the decline of the LBA. Recent studies [12], [22] have suggested that the Sea People raids were the final step in a long and complex spiral of decline in the Eastern Mediterranean world, and that this unstable period was, at least partly, related to environmental causes operating over sizable areas. A climate shift, centred on the 13 th –9 th centuries BC, could not be without consequences on Eastern Mediterranean and West Asian environments where dry farming agro-production, pastoral nomadism and fishing were the primary or secondary subsistence systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation